SUZ12 Loss Amplifies the Ras/ERK Pathway by Activating Adenylate Cyclase 1 in NF1-Associated Neurofibromas - Li, Weijie; Hu, Chenhao; Zhang, Xingnan; Wang, Binbin; Li, Zhen; Ling, Miao; Sun, Shengqiao; Guo, Chao; Li, Dezhi; Liu, Song (Frontiers in Oncology, 2021)
Patients with germline neurofibromatosis type 1 (NF1) microdeletions frequently exhibit hereditary syndromes such as cardiovascular anomalies and have an increased risk of malignant peripheral nerve sheath tumors (MPNSTs). This study aimed to identify the genes codeleted with SUZ12 that are related to MPNST. We used differential gene expression and enrichment analyses to analyze the SUZ12-mutant and SUZ12-wild-type gene expression profiles in the GSE118186 and GSE66743 datasets in Gene Expression Omnibus (GEO). PPI network analysis combined with MPNST patient survival analysis was used to identify ADCY1, which catalyzes the conversion of ATP to cAMP, as a key gene. Moreover, chromatin immunoprecipitation sequencing (ChIP-Seq) showed that the distribution of H3K27me3 in the ADCY1 promoter region and gene body was significantly reduced in SUZ12-mutant cells. To verify the role of ADCY1 in SUZ12 mutation, we used RNA interference and plasmid transfection to interfere with SUZ12 expression in plexiform neurofibroma (pNF) and MPNST cell lines and then treated the cells with forskolin, IBMX and H89. ERK phosphorylation was accelerated and prolonged after siRNA transfection, especially in ipNF05.5 cells, and the intensity and duration of ERK activation were reduced after SUZ12 overexpression. Importantly, the level of p-ERK was consistent with that of Rap1-GTP. Moreover, H89 completely blocked Rap1 activation and the changes in the p-ERK level after SUZ12 siRNA transfection. In conclusion, our findings suggested that SUZ12 loss potentiates the effects of NF1 mutations by amplifying Ras signaling through the ADCY1/cAMP/Rap1/ERK pathway and that SUZ12 may serve as a therapeutic and prognostic biomarker in NF1-associated neurofibromas.